2012
DOI: 10.1007/s10875-012-9650-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the CTLA-4 Gene and Rheumatoid Arthritis Susceptibility: A Meta-analysis

Abstract: This meta-analysis suggested that the +49A/G and CT60 polymorphisms in the CTLA-4 gene may be risk factors for RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
0
18
1
1
Order By: Relevance
“…In the subgroup analysis by ethnicity, results suggested that strong evidences support the association between RA risk and CTLA-4 A49G polymorphism in both Asian and Caucasian populations. Previous meta-analyses works have reported that the CTLA-4 A49G polymorphism is associated with RA risk in Asians, but not in Caucasians using limited data [37,38]. In our work, we performed an up-dated meta-analyses, and found that A49G polymorphism is associated with RA risk in both Asians and Caucasians.…”
Section: Discussionmentioning
confidence: 52%
“…In the subgroup analysis by ethnicity, results suggested that strong evidences support the association between RA risk and CTLA-4 A49G polymorphism in both Asian and Caucasian populations. Previous meta-analyses works have reported that the CTLA-4 A49G polymorphism is associated with RA risk in Asians, but not in Caucasians using limited data [37,38]. In our work, we performed an up-dated meta-analyses, and found that A49G polymorphism is associated with RA risk in both Asians and Caucasians.…”
Section: Discussionmentioning
confidence: 52%
“…Besides, a genetic study has also indicated that there is an association of CTLA-4 gene polymorphism with susceptibility to RA [24]. All these work suggest that co-stimulatory molecule CTLA-4 plays a central role in RA.…”
Section: Discussionmentioning
confidence: 90%
“…The function of gene can be influenced by number of genetic variations, including single nucleotide polymorphisms (SNPs), and resulting in disease phenotypes. Indeed, as evidenced in our previous study and in numerous others, several CTLA-4 polymorphisms that may influence gene expression, lead to amino acid substitution, and alter mRNA splicing have been linked with susceptibility to autoimmune diseases, including autoimmune thyroid diseases, systemic lupus erythematosus, rheumatoid arthritis, and type 1 diabetes [915]. Thus, it is hypothesized that in cancer disease antitumor responses such as proliferation and activation of tumor-specific CTLs may also be altered by genetic polymorphisms in CTLA-4 gene.…”
Section: Introductionmentioning
confidence: 86%